Answer:
f'(x) =
![(-6((e^x - e^(-x)))/((e^x + e^(-x))^4)](https://img.qammunity.org/2021/formulas/mathematics/college/oob2anridn4hxz99uwvy2gw59ccaf1jvc4.png)
Explanation:
Data provided in the question:
f(x) =
![(2)/((e^x + e^(-x))^3)](https://img.qammunity.org/2021/formulas/mathematics/college/qbis84120glhahwk5h96yeuq2lm3bgtnh2.png)
or
we can also write the above equation as:
f(x) = 2 × (eˣ + e⁻ˣ)⁻³
Now,
on differentiating the above equation with respect to 'x', we get
f'(x) = 2 × (-3) × (eˣ + e⁻ˣ)⁻⁴ × (eˣ + (-1)e⁻ˣ)
or
f'(x) =
![(-6((e^x - e^(-x)))/((e^x + e^(-x))^4)](https://img.qammunity.org/2021/formulas/mathematics/college/oob2anridn4hxz99uwvy2gw59ccaf1jvc4.png)
Note: derivative of eˣ = eˣ
derivative of xⁿ = xⁿ⁻¹